2017
DOI: 10.1021/acs.chemmater.7b02116
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Nanocomposites through Nanocrystal Surface Chemistry: Superconducting YBa2Cu3O7 Thin Films via Low-Fluorine Metal Organic Deposition and Preformed Metal Oxide Nanocrystals

Abstract: Achieving low cost, safe, reproducible and high performance superconducting thin films of YBa2Cu3O7-δ is essential to bring this material to the energy market. Here, we report on the chemical solution deposition of YBa2Cu3O7-δ nanocomposites from environmentally benign precursors with a low-fluorine content. Preformed ZrO2 nanocrystals (3.5 nm) were stabilized in a methanolic precursor solution via two strategies: charge stabilization and steric stabilization. Counter-intuitively, charge stabilization did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 52 publications
7
86
1
Order By: Relevance
“…The nucleation and growth of TFA‐based or reduced fluorine‐based YBCO systems can be found in literature and is described as the ex situ BaF 2 process . Generally, it is reported that the formation of BaF 2 instead of BaCO 3 occurs when a fluorine content of more than 15.4% is used .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The nucleation and growth of TFA‐based or reduced fluorine‐based YBCO systems can be found in literature and is described as the ex situ BaF 2 process . Generally, it is reported that the formation of BaF 2 instead of BaCO 3 occurs when a fluorine content of more than 15.4% is used .…”
Section: Resultsmentioning
confidence: 99%
“…In this work, a homogeneous distribution of the ZrO 2 nanocrystals throughout the layer is observed, and no accumulation of ZrO 2 nanocrystals on the LaAlO 3 interface can be observed in the pyrolyzed films as confirmed via TOF‐SIMS analysis (Figure A). The use of a copolymer as stabilization ligand leads to a spread‐out of nanocrystals in the pyrolyzed matrix because of good nanocrystal surface chemistry . This spread‐out of nanocrystals is a very important step to avoid the tendency to accumulations of nanocrystals during the growth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations